2017
DOI: 10.1186/s13098-016-0201-1
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin improves glucose metabolism by Serotonylation of the small GTPase Rab4 in L6 skeletal muscle cells

Abstract: BackgroundSerotonin (5-HT) improves insulin sensitivity and glucose metabolism, however, the underlying molecular mechanism has remained elusive. Previous studies suggest that 5-HT can activate intracellular small GTPases directly by covalent binding, a process termed serotonylation. Activated small GTPases have been associated with increased GLUT4 translocation to the cell membrane. Therefore, we investigated whether serotonylation of small GTPases may be involved in improving Insulin sensitivity and glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 32 publications
3
45
0
Order By: Relevance
“…We then determined whether serotonylation is involved in the induction of PTHrP by using the TG inhibitor, MDC, to reduce serotonylation. Many studies have attributed MDC’s inhibitory effects on signaling pathways to the process of serotonylation [ 35 , 37 , 62 ]. Consistent with our hypothesis, when we combined 5HTP or FLX treatment with MDC, Pthlh expression was decreased and restored to lactogenic control levels, suggesting a TG-dependent serotonylation action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then determined whether serotonylation is involved in the induction of PTHrP by using the TG inhibitor, MDC, to reduce serotonylation. Many studies have attributed MDC’s inhibitory effects on signaling pathways to the process of serotonylation [ 35 , 37 , 62 ]. Consistent with our hypothesis, when we combined 5HTP or FLX treatment with MDC, Pthlh expression was decreased and restored to lactogenic control levels, suggesting a TG-dependent serotonylation action.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown effects at lower concentrations; one study observed that 20μM MDC treatment overnight resulted in a significant decrease in 5HT mitogenesis of distal primary bovine arterial smooth muscle cells, though higher doses (up to 200μM) resulted in larger decreases [ 62 ]. In an additional study it was determined that a 25μM MDC treatment for 3 hours in L6 rat muscle cells results in significant decreases in 5HT-induced effects on GLUT4 translocation, glucose uptake, and glycogen content [ 35 ]. We therefore concluded a lower dose would sufficiently inhibit serotonylation; however, it is likely we would have seen further reductions in PTHrP and a reduction in cAMP concentrations if we used a higher concentration of MDC.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that the metabolic alterations induced by SGAs are partially mediated by hyperphagia linked to alterations in the D1/D2, 5-HT1B, 5-HT2, and 5-HT3 signaling ( 12 ), and GABA2 receptor polymorphism ( 13 ). On this regard, recent research have demonstrated the participation of serotonin signaling in glucose homeostasis through serotonylation of rab4 proteins ( 14 ), moreover other studies have shown that 5HT2 selective antagonism impairs insulin sensitivity. SGAs also induce anomalous cellular differentiation of adipocytes ( 15 ), increase lipid accumulation in the liver tissue ( 16 ), upregulate the sterol regulatory element-binding protein ( 17 ), and inhibit of the glycogen accumulation in skeletal muscle cells ( 18 ).…”
Section: Metabolic Syndrome and Antipsychoticsmentioning
confidence: 99%
“…For example, the GEO expression data set (GDS3688) showed that the PDK4 gene expression of obese was higher than that of controls ( Figure S5 ). Several studies regarding the promoter methylation of PDK4 have indicated the PDK4 methylation levels to negatively correlate with BMI (body mass index) in skeletal muscle samples, and weight loss to be associated with methylation changes of PDK4 promoters [ 47 , 48 , 49 , 50 , 51 , 52 ]. Furthermore, an intergenic variant, rs6465468 nearby the ASB4 gene associated with BMI, is colocalized with PDK4 (about 43.5 kb downstream of PDK4 ( Table 2 and Figure S6a )) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%